KONCEPCJA UCZENIA SIĘ PRZEZ NAUCZANIE INNYCH (LDL) W KSZTAŁCENIU NAUCZYCIELI JĘZYKA NIEMIECKIEGO - Białek, Magdalena (Neofilolog, 2019)
The subject of this article is the concept of learning by teaching used for the training of teachers of German. Foreign language teacher training is currently no doubt one of the most important challenges resulting from the educational policies of countries within the European Union. In Poland, the necessity for remedial, preventive or promotional actions with regard to the teaching of foreign languages seems to pertain first of all to the teachers of German (and their training facilities), as the justification for German’s presence in the Polish schools is increasingly being questioned. Unfortunately, there are numerous examples in school practice which show that the contemporary approach to the teaching of German as a foreign language continues to follow a traditional, transmission model, with great perseverance and consistency. In order to change this situation, it is necessary to find some effective educational solutions for foreign language teacher training. The search should focus on those educational tools which will enable teachers-tobe to meet their teaching goals and conduct the teaching process in line with the current theories of language teaching. One of many such tools, which I have decided to examine more closely, is the concept of learning by teaching (Lernen durch Lehren), initiated by Jean Pol Martin. This paper presents the main assumptions of the concept of LdL and describes a training programme (developed following the LdL approach) carried out with the students of faculty of German who are future teachers of German. The conclusions drawn seem quite promising for teacher training.